Emotional intelligence and job satisfaction among repatriates: repatriation adjustment as a mediator - James, R. (Inderscience Enterprises Ltd., 2021)
Job satisfaction is a crucial variable that positively influences personal and organisational outcomes. The influence of emotional intelligence on employee satisfaction has been well documented in the literature, but lack of studies found such research among repatriates. This study aims to investigate the influence of repatriates’ emotional intelligence on job satisfaction through repatriation adjustment. The study was conducted with 96 repatriates who have at least two years of expatriation experiences. The proposed relationship was assessed through structural equation modelling with SmartPLS. This study found that emotional intelligence enables repatriates to adjust their repatriation transition better and better adjustment enhances their job satisfaction. Unexpectedly the proposed relationship between emotional intelligence and satisfaction was not significant as expected. However, this study found that the relationship between emotional intelligence and satisfaction absorbed by repatriation adjustment. This study contributes to the literature by empirically investigating the relationship between emotional intelligence and satisfaction among repatriates and by introducing adjustment as a mediator on this relationship. The implication for organisation and individual, limitations of the study and avenue for future research has been discussed.
Keywords: Emotional intelligence; Satisfaction; Repatriates; Repatriation; Adjustment; Transition; Expatriation